Eu amo violino! crianças de escola pública que estudam violino - Mattos, Sandra Carvalho de (2011)
Violin, which at first seems very far away from the kids today, especially children who study in public schools, may not be as far as their knowledge of the senses. The violin is the representative of the orchestra in a timely manner and appears repeatedly in television programs and concerts in parks. In compiling this work I focused on children as young as nine years studying in EMEF Esperidião Rosas School in West São Paulo. Whenever there was announcement of free lessons violin demand was great. This thesis seeks to understand the reason for this demand, and from this question, describe the relationship of the daily study of this instrument, the relationship between the people who surround the children, the relationship between instrument and body of children, and finally the relationship of children with sound